Reaksi Pasar Modal Indonesia Sebelum dan Sesudah Pengumuman Paket Kebijakan Ekonomi XVI pada Saham Sektor Pertambangan yang Terdaftar Di Bursa Efek Indonesia Tahun 2018 - Erni Alfisah (Islamic University of Kalimantan MAB Banjarmasin, 2020)
This research is aimed to analyze and understand the difference in the average abnormal return (AAR) and the average trading volume activity (ATVA) with several periods of observation both before or after the announcement of the economic policy package XVI in the mining sector included on the Stock Exchange in 2018 is the research objective. Event study is a type of research used. The announcement of the economic policy package XVI is a test event. The study requires secondary data which includes data on daily closing price, trading volume, and the number of shares outstanding from the mining sector samples being sampled. After the paired samples t-test was tested differently it was stated that there were no differences in observations 5 days & 10 days before and 5 days & 10 days after the announcement of the economic policy package XVI, at ATVA 10 days before & 10 days after the economic policy package XVI was found differences ATVAKeywords: AAR (average abnormal return), ATVA (average trading volume activity), Announcement of Economic Policy Package XVI 2018, event studies.